2021
DOI: 10.1021/acsami.1c10872
|View full text |Cite
|
Sign up to set email alerts
|

High Performance of Anion Exchange Blend Membranes Based on Novel Phosphonium Cation Polymers for All-Vanadium Redox Flow Battery Applications

Abstract: The deployment of alkaline anion exchange membranes (AEMs) in flow battery applications has the advantage of a low cationic species crossover rate. However, the alkaline stability conjugated to the low conductivity of hydroxide ions of anion exchange membranes (AEMs) still represents a major drawback for the large deployment of such technology. In this study, three types of tetraarylpolyphosphonium (pTAP)-based copolymers (namely, CP1, CP2, and CP3) are synthesized and blended with chitosan and polyvinylidene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…[2] However, the extensive industrialization and the sustainable deployment of AEM-WEs are thought to be hampered by the unavailability of highly durable and high-performance AEMs (like Nafion ® utilized in PEM-WEs). Since the last few years, there has been a great interest in the development and exploration of synthetic pathways of novel AEMs for applications in electrochemical energy storage and conversion devices such as AEM-WEs, metal-air batteries, [3] redox flow batteries, [4] and anion exchange membrane fuel cells. [5] AEMs are composed of a polymer backbone, functional cationic groups, and free counterions.…”
Section: Introductionmentioning
confidence: 99%
“…[2] However, the extensive industrialization and the sustainable deployment of AEM-WEs are thought to be hampered by the unavailability of highly durable and high-performance AEMs (like Nafion ® utilized in PEM-WEs). Since the last few years, there has been a great interest in the development and exploration of synthetic pathways of novel AEMs for applications in electrochemical energy storage and conversion devices such as AEM-WEs, metal-air batteries, [3] redox flow batteries, [4] and anion exchange membrane fuel cells. [5] AEMs are composed of a polymer backbone, functional cationic groups, and free counterions.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium redox flow batteries (VRFBs) are fascinating because of their durability, high consistency, rapid response, and decoupled capacity configuration. For VRFB, the key component is the membrane to separate the anolyte (V 2+ /V 3+ ) and catholyte (VO 2+ /VO 2 + ), along with the accomplishment of the circuit to conduct protons. A well-performing membrane should possess elevated stabilities, high ionic conductivity, truncated vanadium ion permeability, and a cost-effective nature. , Various cation-exchange membranes (CEMs) based on sulfonated nonfluorinated polymers suffered because of deprived dimensional, mechanical, and chemical stabilities in the hydrated state. Fluorinated polymer-based CEMs like Nafion are widely used in VRFB because of their high chemical stability and high conductivity. In contrast, the Nafion separator experiences some stern drawbacks like high cost, severe self-discharge, large capacity loss, electro-osmotic drag, reduced ion selectivity, and swift vanadium crossover that are responsible for reduced battery performance. Therefore, considerable effort has been expended to adapt the fluorinated CEMs for VRFB application. Poly­(vinylidene fluoride- co -hexafluoropropylene) (PVDF- co -HFP) is a block copolymer and is regarded as a material with a strong C–F bond that gives outstanding stabilities and a crystalline structure for reducing vanadium-ion penetration. , Various macromolecular amendments of PVDF- co -HFP either by grafting or by blending of ionic moieties have been reported. A high degree of functionality can often be achieved by the blending of miscible polymers as a result of synergistic effects; , nevertheless, ionic moieties percolated, resulting in the deterioration of membrane conductivity. , Thus, grafting of a functional monomer has been considered a viable option for constructing CEMs . It has been found that the grafting of aromatic moieties such as 4-hydroxybenzenesulfonic acid further degrades membrane stability. , …”
Section: Introductionmentioning
confidence: 99%
“…23,24 Various macromolecular amendments of PVDF-co-HFP either by grafting or by blending of ionic moieties have been reported. 25−27 A high degree of functionality can often be achieved by the blending of miscible polymers as a result of synergistic effects; 28,29 nevertheless, ionic moieties percolated, resulting in the deterioration of membrane conductivity. 30,31 Thus, grafting of a functional monomer has been considered a viable option for constructing CEMs.…”
Section: Introductionmentioning
confidence: 99%
“…Anion exchange membranes (AEMs) have drawn great interest from researchers because of their essential role in a wide range of electrochemical devices, including anion exchange membrane fuel cells (AEMFCs) [1,2], redox flow batteries [3] and water electrolyzers [4]. The items determine the performance of these electrochemical devices directly [5].…”
Section: Introductionmentioning
confidence: 99%